Epidemiology and clinicopathological features of soft tissue tumors in adolescents: a cross-sectional study - Ogochukwu Chioma Ofiaeli; Felix Emeka Menkiti; Victor Ifeanyichukwu Modekwe; Shirley Nneka Chukwurah; Ogochukwu Robinson Ofiaeli; Amalachukwu Okwukweka Odita (BMC Pediatrics)
Abstract Background Soft tissue tumors (STTs) in adolescents are relatively rare, and their characteristics and behavior have not been well studied in this age group. The aim of this study was to describe the clinicopathologic patterns of STTs in adolescents aged 10–19 years according to the 2020 WHO classification. Method A 10-year retrospective cross-sectional study of 632 surgical samples from adolescents was conducted at a tertiary health facility to determine the frequency, histological patterns and characteristics of STTs in this population. The data were analyzed via SPSS 23. Results STTs accounted for 12.5% of all histologically diagnosed lesions in adolescents, with a mean age of 15 ± 2.9 years, 54.4% occurring in females and 35.4% in middle adolescents. The majority (64.56%) of STTs were benign, while malignant and intermediate-grade neoplasms accounted for 25.32% and 10.13%, respectively. Vascular tumours were the most common, followed by adipocytic and fibroblastic/myofibroblastic tumours, with hemangiomas being the most common. The most prevalent symptom was a painless mass (82.3%), with the head and neck (25.3%) being the most commonly involved body site. Most of the STTs patients presented within the first two years of occurrence (36.7%, n = 29/79). However, age, age group and sex were not significantly associated with the WHO grades of these STTs. Conclusion This study provided valuable insights into the characteristics and behavior of STTs in adolescents, highlighting the importance of early diagnosis and management. These findings suggest that adolescent STTs affect females more than males , involve the head and neck more and are more benign, with vascular tumours being the most common type of STT in this age group.